A8 Large animal models in huntington's disease: conceptual overview: what model to use for what purpose. (13th September 2016) - Howland, David
Abstract : The dominant nature of the Huntington's disease (HD) gene mutation has allowed genetic model development in multiple species, with the mutation in all cases causing an abnormal neurological phenotype. Mouse models are most widely used (i.e. R6/2 transgenic and Q175 knock-in) in research as they show relatively rapid and progressive neurological phenotypes but have been questioned in the context of the adult-onset disease that takes years to manifest in humans. There is no doubt that we have and continue to learn much from rodent models, but their usefulness is limited by two species constraints; the brains of rodents differ significantly from humans in small size and neuroanatomical organisation and rodents have much shorter lifespans than humans. Large animal models (sheep, minipigs and nonhuman primates) expressing mutant HTT help alleviate these constraints and should be used to fill specific niches in preclinical HD research including studying disease natural history, in particular neurophysiology and histopathology, where such analyses are only of limited value in the small lissencephalic mouse brain and are not possible in human subjects. This may be particularly relevant in mapping the progression of disease in the premanifest stages, data which is lacking from patients. Importantly, testing of new therapeutic agents including nucleic acid and gene-based therapies (i.e. targeting mutant HTT) in the large-brain is imperative to elucidate when and where these therapies need be administered to obtain maximal therapeutic effect as well as to determine long term safety. Preclinical research using large animals is expensive, takes much longer than working in mouse models and is limited in that these models are not easily accessible by all investigators. Further, the multiple large animal species afford different added values but also have specific limitations. Recognising and embracing these differences is key to a sound strategic implementation of the various existing large animal models in preclinical research.